INSTRUMENTAL ANALYSIS OF NOVEL SIDDHA FORMULATION POONAGA PARPAM (International Journal of Ayurveda and Pharma Research, 2019)
Poonaga parpam (PNP) is an animal origin siddha formulation mentioned in the Siddha text “Sikicha Rathina Deepam”. The trial drug was prepared as per the standard operative procedure and subjected to various studies to reveal its potency. Materials and methods: The aim of the study was to standardize the PNP by modern instrumental techniques such as Fourier Transform Infra-Red Spectroscopy (FTIR), Inductively Coupled Plasma Optical Emission Spectroscopy (ICPOES), Scanning Electron Microscope with Energy Dispersive X-Ray Analysis (SEM with EDAX), X-Ray Diffractometer (XRD), Thermo Gravimetric Analysis (TGA). Results and Discussion: ICP-OES revealed the heavy metals like As, Cd, Pb, Hg and trace element like Ni were below detectable level. The stretches and bonds present in the FTIR analysis indicated the presence of some organic functional groups such as alcohol, aromatic, alkane, carbonyl, ketone, alkane, amine and alkyl halide which may be the reason for the therapeutic potency of the drug. XRD results revealed that the copper and iron may be the key ingredients present in the test drug PNP and the SEM picture indicated the existence of nanoparticles. TGA results revealed that the test drug PNP seems to be stable at varying temperature ranges from 50 to 400°C. Based on the results, Poonaga Parpam is preferably non-toxic to human in its therapeutic dose.